Significance of exponential space‐based heat source and inclined magnetic field on heat transfer of hybrid nanoliquid with homogeneous–heterogeneous chemical reactions. Issue 4 (26th January 2021) - Al‐Kouz, Wael; Swain, Kharabela; Mahanthesh, Basavarajappa; Jamshed, Wasim
Abstract: Many chemical reactive methods, like combustion, catalysis, and biochemical involve homogeneous–heterogeneous chemical reaction (HHCR). The collaboration among the heterogeneous and homogeneous reactions is exceedingly multifarious, including the creation and depletion both within the liquid and catalytic surfaces. Here, we observe the influences of Cu and Al2 O3 nanoparticles past an elongating sheet under HHCR. An inclined magnetic field with an acute angle is applied to the direction of the flow. Further, radiative heat, temperature, and exponential space‐based heat source aspects are modifying the thermal equation. The governing nonlinear equations are deciphered by utilizing the Runge–Kutta‐based shooting method. It is found that HHCR reduces the solute layer thickness, whereas the increase in the angle of inclination of applied magnetism thickens momentum layer thickness.